Desire: Flaubert, Proust, Fitzgerald, Miller, Lana Del Rey - Grande, Per Bjørnar (Breakthroughs in mimetic theory, 2020)
"Desire: Flaubert, Proust, Fitzgerald, Miller, Lana Del Rey is about understanding how desire works in our lives"--